To Anatoly Stepanovich Skripkin – Scientist, Teacher and Friend - Valeriy M. Klepikov; Alexandr N. Djachenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Anatoly S. Skripkin, Doctor of Historical Sciences, Professor is turning 80 this year. Anatoly S. Skripkin is one of the prominent experts in the field of Sarmatian archaeology. He has started his research in the 60s of the 20th century and made a huge contribution to the study of Early, Middle and Late Sarmatian cultures. His articles and monographs are well known in the scientific world. Having carefully studied the features of the funeral rite, accompanying inventory, and built the chronology and periodization of Sarmatian history, he consistently moved to ethnohistorical reconstructions, offering a complex and logical picture of the history of Iranian-speaking nomadic peoples of the Eurasian steppes in the Early Iron Age. At the same time, Anatoly S. Skripkin became one of the founders of Volgograd archaeology, forming a close-knit team of scientists involved in various areas of Sarmatian history, including interdisciplinary research. He was also one of the first teachers and organizers of young Volgograd State University. The scientist s achievements were appreciated by the management and scientific community – Anatoly S. Skripkin is an Honorary Worker of Higher Professional Education of the Russian Federation, an Honored Scientist of the Russian Federation, and has received many awards. Despite his age, the researcher actively participates in science projects, supervises the training of postgraduate students, and takes part in expeditions. He is a tireless traveler. His visit to India, teaching in China and his travels in Egypt have given precise observations to lectures on the history of the Ancient East, and have given a different perspective to his works on the contacts of the Sarmatian world with eastern countries. We congratulate the dear anniversary celebrant on his birthday, wish him strength, health and new creative achievements.